HABITUS DAN LINTASAN DHARMADI DALAM EKSISTENSI KEPENYAIRAN SASTRA BANYUMAS - Nila Mega Marahayu; Octaria Putri Nurharyani; Bivit Anggoro Prasetyo Nugroho (Bahtera Indonesia, 2022)
literature’s treasures. Therefore, it is necessary to study in full by examining the poet's biography, relations and acknowledgement, as well as awards and ideological thoughts of the poets. Dharmadi is a part of the local literature of Banyumas’ poet by instilling and determining his position as a poet with a long process to gain legitimacy. The purpose of this study is to perpetuate the assets of Banyumas' local literary treasures and provide the alternative resources in viewing Banyumas literature from the genre of poem and poetry. This study uses a qualitative descriptive method with the theory is the sociological literary criticism of the cultural production arena by Pierre Bourdieu. The results of this research show that the habitus and trajectory are strong supporting factors in Dharmadi's existence of the literary poetry in Banyumas arena. Dharmadi's habitus consists of three elements; historical products habitus, preconscious habitus, regular and patterned habitus. In addition, finding the trajectory of Dharmadi which is individual as a route in the poet's journey to reach the position of the poet in the arena of Banyumas cultural production.